Thermomechanical Joining of Hypoeutectic Aluminium Cast Plates - Borgert, Thomas; Neuser, Moritz; Hoyer, Kay-Peter; Homberg, Werner; Schaper, Mirko (Journal of Manufacturing and Materials Processing)
Consistent lightweight construction in the area of vehicle manufacturing requires the increased use of multi-material combinations. This, in turn, requires an adaptation of standard joining techniques. In multi-material combinations, the importance of integral cast components, in particular, is increasing and poses additional technical challenges for the industry. One approach to solve these challenges is adaptable joining elements manufactured by a thermomechanical forming process. By applying an incremental and thermomechanical joining process, it is possible to react immediately and adapt the joining process inline to reduce the number of different joining elements. In the investigation described in this publication, cast plates made of the cast aluminium alloy EN AC-AlSi9 serve as joining partners, which are processed by sand casting. The joining process of hypoeutectic AlSi alloys is challenging as their brittle character leads to cracks in the joint during conventional mechanical joining. To solve this, the frictional heat of the novel joining process applied can provide a finer microstructure in the hypoeutectic AlSi9 cast alloy. In detail, its Si is finer-grained, resulting in higher ductility of the joint. This study reveals the thermomechanical joining suitability of a hypoeutectic cast aluminium alloy in combination with adaptively manufactured auxiliary joining elements.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Mechanics of Materials

Auslegungsmethode zum Kleben höchstfester Stahlwerkstoffe im Landmaschinenbau - Göddecke, Johannes; Göhrs, Tim; Meschut, Gerson; Große Gehling, Manfred (Stahlbau)
Abstract In Konstruktionen des Landmaschinenbaus aus dickeren Blechen (ca. 3–10 mm) findet die Klebtechnik bislang nur wenig Anwendung, obwohl sie in anderen Einsatzgebieten bereits ein etabliertes Fügeverfahren darstellt und viele Vorteile gegenüber anderen Fügeverfahren bietet, da es bisher an Regelwerken bei der Auslegung derartiger Verbindungen fehlt. Ein wesentliches Kriterium bei der Auslegung von Verbindungen im Landmaschinenbau ist die Ermüdungsfestigkeit aufgrund der langen Nutzungsphase der Produkte und der in der Landtechnik vorherrschenden Belastungscharakteristika. Geklebte Verbindungen weisen ein hervorragendes Verhalten bei zyklischer Belastung auf. Die steigenden Anforderungen im Hinblick auf Ressourceneffizienz und Leichtbau führen zu einem Umdenken, da durch den vermehrten Einsatz höherfester Stahlwerkstoffe in Kombination mit der Klebtechnik dieses als umsetzbar erscheint. Ziel ist die Entwicklung einer Methode zur Auslegung geklebter Verbindungen in Konstruktionen mit höherfesten Stahlwerkstoffen in Anlehnung an die FKM‐Richtlinie. Die betriebsrelevanten Beanspruchungen der Landtechnik werden analysiert und an speziellen Probekörpern untersucht. Dabei werden sowohl die mechanischen, thermischen und medialen Einflussfaktoren als auch der Einfluss der Klebfugengeometrie und von Betriebslastenkollektiven untersucht. Die Erkenntnisse werden in einer KMU‐relevanten Vorgehensweise zur Ermittlung von Abminderungsfaktoren zusammengefasst, wodurch die Auslegung der Bauteilfestigkeit sowohl statisch als auch dynamisch möglich ist.
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials; Building and Construction; Civil and Structural Engineering

Measurement, Modelling, and Appli cation of Lubricant Properties at Extreme Pressures - Wingertszahn, Patrick; Schmitt, Sebastian; Thielen, Stefan; Oehler, Manuel; Magyar, Balázs; Koch, Oliver; Hasse, Hans; Stephan, Simon (Tribologie und Schmierungstechnik)
Lubricants play a central role in many technical applications, e.g. in bearings and gears as well as in machining processes. In such applications, lubricants are exposed to extreme conditions in the contact area. In lubrication gaps, the pressure can reach values up to 5 GPa. The thermophysical properties of lubricants, and in particular the viscosity, at such extreme conditions have an important influence on the friction and wear behavior of a tribosystem. Accordingly, reliable lubricant property models are a prerequisite for accurate tribological simulations, e.g. elastohydrodynamic lubrication (EHL) simulations. Presently, the vast majority of experimental thermophysical property data are only available up to 1 GPa. Thus, reliable and robust models with strong extrapolation capabilities to higher pressure are required. In this work, viscosity measurements of squalane in a temperature range be tween 20 °C and 100 °C and pressures up to 1 GPa were carried out. Based on that data, a physical model for the viscosity was developed. The model is built by combining a molecular-based equation of state with the so-called entropy scaling approach. Finally, we demonstrate how this fluid property model can be favorably integrated in an EHL simulation by an application programming interface (API). The novel hybrid modeling approach is promising for future applications.
Keywords: Surfaces; Coatings and Films; Surfaces and Interfaces; Mechanical Engineering; Mechanics of Materials

Adaptive Scaling of Components in the Fused Deposition Modeling Process - Moritzer, Elmar; Hecker, Felix (Macromolecular Symposia)
Abstract Currently, the fused deposition modeling (FDM) process is the most common additive manufacturing technology. The principle of the FDM process is the strand wise deposition of molten thermoplastic polymers, by feeding a filament trough a heated nozzle. Due to the strand and layer wise deposition the cooling of the manufactured component is not uniform. This leads to dimensional deviations which may cause the component to be unusable for the desired application. In this paper, a method is described which is based on the shrinkage compensation through the adaption of every single raster line in components manufactured with the FDM process. The shrinkage compensation is based on a model resulting from a DOE which considers the main influencing factors on the shrinkage behavior of raster lines in the FDM process. An in‐house developed software analyzes the component and locally applies the shrinkage compensation with consideration of the boundary conditions, e.g., the position of the raster line in the component and the process parameters. Following, a validation using a simple geometry is conducted to show the effect of the presented adaptive scaling method.
Keywords: Materials Chemistry; Polymers and Plastics; Organic Chemistry; Condensed Matter Physics

Assessing the Impact of the Powder Production Method on Ceramic-filled Polyamide Composites made by Laser Sintering - Kletetzka, Ivo; Neitzel, Fabian; Schmid, Hans-Joachim (Proceedings of the 34th Annual International Solid Freeform Fabrication Symposium)
Polymer composites represent the industry standard in injection molding for the production of plastic components with increased requirements in terms of heat resistance and stiffness. In the field of laser sintering (LS), these materials are less common so far. In order to extend the available material variety for the LS process, new ceramic-filled Polyamide 613 powders are investigated within the scope of this work. Here, the resulting properties from two different powder production methods are compared. One filled powder is produced by dry blending and the other powder with the same filler and filling ratio is produced by encapsulating the filler particles inside the polymer particles within the dissolution-precipitation process. It was found that encapsulating the filler particles can provide certain benefits for the processability, for example an improved powder flowability or better filler dispersion. However, encapsulating the filler also alters the thermal properties of the precipitated powder.
Keywords: Additive Manufacturing; Laser Sintering; Filled Materials; Composites; Polyamide 613

Antimicrobial Brushes on Titanium via “Grafting to” Using Phosphonic Acid/Pyridinium Containing Block Copolymers - Methling, Rafael; Dückmann, Oliver; Simon, Frank; Wolf‐Brandstetter, Cornelia; Kuckling, Dirk (Macromolecular Materials and Engineering)
Abstract Coating medical implants with antibacterial polymers may prevent postoperative infections which are a common issue for conventional titanium implants and can even lead to implant failure. Easily applicable diblock copolymers are presented that form polymer brushes via “grafting to” mechanism on titanium and equip the modified material with antibacterial properties. The polymers carry quaternized pyridinium units to combat bacteria and phosphonic acid groups which allow the linear chains to be anchored to metal surfaces in a convenient coating process. The polymers are synthesized via reversible‐addition‐fragmentation‐chain‐transfer (RAFT) polymerization and postmodifications and are characterized using NMR spectroscopy and SEC. Low grafting densities are a major drawback of the “grafting to” approach compared to “grafting from”. Thus, the number of phosphonic acid groups in the anchor block are varied to investigate and optimize the surface binding. Modified titanium surfaces are examined regarding their composition, wetting behavior, streaming potential, and coating stability. Evaluation of the antimicrobial properties revealed reduced bacterial adhesion and biofilm formation for certain polymers, albeit the cell biocompatibility against human gingival fibroblasts is also impaired. The presented findings show the potential of easy‐to‐apply polymer coatings and aid in designing next‐generation implant surface modifications.
Keywords: Materials Chemistry; Polymers and Plastics; Organic Chemistry; General Chemical Engineering

Spectral and Energy Efficiency Maximization of MISO STAR-RIS-Assisted URLLC Systems - Soleymani, Mohammad; Santamaria, Ignacio; Jorswieck, Eduard A. (IEEE Access)
Keywords: General Engineering; General Materials Science; General Computer Science; Electrical and Electronic Engineering

Nonlinear Dielectric Geometric-Phase Metasurface with Simultaneous Structure and Lattice Symmetry Design - Liu, Bingyi; Geromel, René; Su, Zhaoxian; Guo, Kai; Wang, Yongtian; Guo, Zhongyi; Huang, Lingling; Zentgraf, Thomas (ACS Photonics)
In this work, we utilize thin dielectric meta-atoms placed on a silver substrate to efficiently enhance and manipulate the third-harmonic generation. We theoretically and experimentally reveal that when the structural symmetry of the meta-atom is incompatible with the lattice symmetry of an array, some generalized nonlinear geometric phases appear, which offers new possibilities for harmonic generation control beyond the accessible symmetries governed by the selection rule. The underlying mechanism is attributed to the modified rotation of the effective principal axis of a dense meta-atom array, where the strong coupling among the units gives rise to a generalized linear geometric phase modulation of the pump light. Therefore, nonlinear geometric phases carried by third-harmonic emissions are the natural result of the wave-mixing process among the modes excited at the fundamental frequency. This mechanism further points out a new strategy to predict the nonlinear geometric phases delivered by the nanostructures according to their linear responses. Our design is simple and efficient and offers alternatives for the nonlinear meta-devices that are capable of flexible photon generation and manipulation.
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics; Biotechnology; Electronic; Optical and Magnetic Materials

Influence of thermomechanical processing on the microstructural and mechanical properties of steel 22MnB5 - Reitz, A.; Grydin, O.; Schaper, M. (Materials Science and Engineering: A)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Second Harmonic Optical Circular Dichroism of Plasmonic Chiral Helicoid-III Nanoparticles - Spreyer, Florian; Mun, Jungho; Kim, Hyeohn; Kim, Ryeong Myeong; Nam, Ki Tae; Rho, Junsuk; Zentgraf, Thomas (ACS Photonics)
While plasmonic particles can provide optical resonances in a wide spectral range from the lower visible up to the near-infrared, often, symmetry effects are utilized to obtain particular optical responses. By breaking certain spatial symmetries, chiral structures arise and provide robust chiroptical responses to these plasmonic resonances. Here, we observe strong chiroptical responses in the linear and nonlinear optical regime for chiral L-handed helicoid-III nanoparticles and quantify them by means of an asymmetric factor, the so-called g-factor. We calculate the linear optical g-factors for two distinct chiroptical resonances to −0.12 and –0.43 and the nonlinear optical g-factors to −1.45 and −1.63. The results demonstrate that the chirality of the helicoid-III nanoparticles is strongly enhanced in the nonlinear regime.
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics; Biotechnology; Electronic; Optical and Magnetic Materials

Size‐Dependent Strain Relaxation in InAs Quantum Dots on Top of GaAs(111)A Nanopillars - Riedl, Thomas; Kunnathully, Vinay S.; Trapp, Alexander; Langer, Timo; Reuter, Dirk; Lindner, Jörg K. N. (Advanced Materials Interfaces)
Keywords: Mechanical Engineering; Mechanics of Materials

Conformal Pressure and Fast-Charging Li-Ion Batteries - Cao, Chuntian; Steinrück, Hans-Georg; Paul, Partha P; Dunlop, Alison R.; Trask, Stephen E.; Jansen, Andrew; Kasse, Robert M; Thampy, Vivek; Yusuf, Maha; Nelson Weker, Johanna; Shyam, Badri; Subbaraman, Ram; et al. (Journal of The Electrochemical Society)
Abstract Batteries capable of extreme fast-charging (XFC) are a necessity for the deployment of electric vehicles. Material properties of electrodes and electrolytes along with cell parameters such as stack pressure and temperature have coupled, synergistic, and sometimes deleterious effects on fast-charging performance. We develop a new experimental testbed that allows precise and conformal application of electrode stack pressure. We focus on cell capacity degradation using single-layer pouch cells with graphite anodes, LiNi0.5Mn0.3Co0.2O2 (NMC532) cathodes, and carbonate-based electrolyte. In the tested range (10 – 125 psi), cells cycled at higher pressure show higher capacity and less capacity fading. Additionally, Li plating decreases with increasing pressure as observed with scanning electron microscopy (SEM) and optical imaging. While the loss of Li inventory from Li plating is the largest contributor to capacity fade, electrochemical and SEM examination of the NMC cathodes after XFC experiments show increased secondary particle damage at lower pressure. We infer that the better performance at higher pressure is due to more homogenous reactions of active materials across the electrode and less polarization through the electrode thickness. Our study emphasizes the importance of electrode stack pressure in XFC batteries and highlights its subtle role in cell conditions.
Keywords: Materials Chemistry; Electrochemistry; Surfaces; Coatings and Films; Condensed Matter Physics; Renewable Energy; Sustainability and the Environment; Electronic; Optical and Magnetic Materials

Corrosion fatigue behavior of electron beam melted iron in simulated body fluid - Wackenrohr, Steffen; Torrent, Christof Johannes Jaime; Herbst, Sebastian; Nürnberger, Florian; Krooss, Philipp; Ebbert, Christoph; Voigt, Markus; Grundmeier, Guido; Niendorf, Thomas; Maier, Hans Jürgen (npj Materials Degradation)
Abstract Pure iron is very attractive as a biodegradable implant material due to its high biocompatibility. In combination with additive manufacturing, which facilitates great flexibility of the implant design, it is possible to selectively adjust the microstructure of the material in the process, thereby control the corrosion and fatigue behavior. In the present study, conventional hot-rolled (HR) pure iron is compared to pure iron manufactured by electron beam melting (EBM). The microstructure, the corrosion behavior and the fatigue properties were studied comprehensively. The investigated sample conditions showed significant differences in the microstructures that led to changes in corrosion and fatigue properties. The EBM iron showed significantly lower fatigue strength compared to the HR iron. These different fatigue responses were observed under purely mechanical loading as well as with superimposed corrosion influence and are summarized in a model that describes the underlying failure mechanisms.
Keywords: Materials Chemistry; Materials Science (miscellaneous); Chemistry (miscellaneous); Ceramics and Composites

Efficient Frequency Conversion with Geometric Phase Control in Optical Metasurfaces - Reineke Matsudo, Bernhard; Sain, Basudeb; Carletti, Luca; Zhang, Xue; Gao, Wenlong; Angelis, Costantino; Huang, Lingling; Zentgraf, Thomas (Advanced Science)
Keywords: General Physics and Astronomy; General Engineering; Biochemistry; Genetics and Molecular Biology (miscellaneous); General Materials Science; General Chemical Engineering; Medicine (miscellaneous)

Consideration of the manufacturing history of sheet metal components for the adaptation of a clinching process - Heyser, Per; Wiesenmayer, S; Frey, P; Nehls, T; Scharr, C; Flügge, W; Merklein, M; Meschut, Gerson (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)
The process chain for the manufacturing of sheet metal components in mass production includes various cutting and forming operations, which influence the resulting properties of the parts and therefore subsequent manufacturing steps, such as clamping and joining. It is shown that clamping of the components leads to superimposed residual stresses and geometry changes. Therefore, the part properties differ from the initial state of the semifinished products, which has to be considered in the design of clinched joints. This paper presents an approach for coupled determination of the properties of semifinished and finished parts during deep drawing and clamping as well as their effects on the joint quality during clinching. One method for the effective and efficient determination of the properties of semifinished products and components during production is using process data from the preceding manufacturing processes, which is concretely presented in this work. In addition to the interconnection of the entire production chain, it is necessary to define relevant process data for each individual manufacturing step and to correlate the data with the material properties reliably. Therefore, the cross-process interactions of different steps of the process chain for the manufacturing of sheet metal components and the effect of process variations on subsequent manufacturing steps are investigated. Consequently, the boundary conditions for a mechanical joining process based on data from preceding process steps can be predicted.
Keywords: Mechanical Engineering; General Materials Science

Environment‐Dependent Stability and Mechanical Properties of DNA Origami Six‐Helix Bundles with Different Crossover Spacings - Xin, Yang; Piskunen, Petteri; Suma, Antonio; Li, Changyong; Ijäs, Heini; Ojasalo, Sofia; Seitz, Iris; Kostiainen, Mauri A.; Grundmeier, Guido; Linko, Veikko; Keller, Adrian (Small)
Keywords: Biomaterials; Biotechnology; General Materials Science; General Chemistry

Remote epitaxy of InxGa1-xAs (0 0 1) on graphene covered GaAs(0 0 1) substrates - Henksmeier, T.; Schulz, J.F.; Kluth, E.; Feneberg, M.; Goldhahn, R.; Sanchez, A.M.; Voigt, M.; Grundmeier, Guido; Reuter, Dirk (Journal of Crystal Growth)
Keywords: Materials Chemistry; Inorganic Chemistry; Condensed Matter Physics

Influence of hydrogel coatings on corrosion and fatigue of iron in simulated body fluid - Huang, Jingyuan; Voigt, Markus; Wackenrohr, Steffen; Ebbert, Christoph; Keller, Adrian; Maier, Hans Jürgen; Grundmeier, Guido (Materials and Corrosion)
Keywords: Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; Mechanical Engineering; Mechanics of Materials; Environmental Chemistry; Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; Mechanical Engineering; Mechanics of Materials; Environmental Chemistry; Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; Mechanical Engineering; Mechanics of Materials; Environmental Chemistry

Effect of Surface Hydrophobicity on the Adsorption of a Pilus-Derived Adhesin-like Peptide - Yang, Yu; Huang, Jingyuan; Dornbusch, Daniel; Grundmeier, Guido; Fahmy, Karim; Keller, Adrian; Cheung, David L. (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Multimodal quantification of degradation pathways during extreme fast charging of lithium-ion batteries - McShane, Eric J.; Paul, Partha P.; Tanim, Tanvir R.; Cao, Chuntian; Steinrück, Hans-Georg; Thampy, Vivek; Trask, Stephen E.; Dunlop, Alison R.; Jansen, Andrew N.; Dufek, Eric J.; Toney, Michael F.; Weker, Johanna Nelson; et al. (Journal of Materials Chemistry A)
Using a unique combination of advanced characterization techniques, we identify specific degradation mechanisms and quantify degradative species formed during fast charge cycling of lithium-ion battery pouch cells.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry